Glycyrrhizic Acid Nanoparticles Subside the Activity of Methicillin-Resistant Staphylococcus aureus by Suppressing PBP2a - Patricia Rijo; Tamer M. M. Abuamara; Lashin Saad Ali Lashin; Sherif A. Kamar; Vera M. S. Isca; Tahseen S. Mohammed; Mohamed S. M. Abdrabo; Mohamed A. Amin; Ahmed I. Abd El Maksoud; Amr Hassan (MDPI AG, 2024)
Staphylococcus aureus and methicillin-resistant Staphylococcus aureus (MRSA) are classified as high-risk infections that can lead to death, particularly among older individuals. Nowadays, plant nanoparticles such as glycyrrhizic acid are recognized as efficient bactericides against a wide range of bacterial strains. Recently, scientists have shown interest in plant extract nanoparticles, derived from natural sources, which can be synthesized into nanomaterials. Interestingly, glycyrrhizic acid is rich in antioxidants as well as antibacterial agents, and it exhibits no adverse effects on normal cells. In this study, glycyrrhizic acid nanoparticles (GA-NPs) were synthesized using the hydrothermal method and characterized through physicochemical techniques such as UV-visible spectrometry, DLS, zeta potential, and TEM. The antimicrobial activity of GA-NPs was investigated through various methods, including MIC assays, anti-biofilm activity assays, ATPase activity assays, and kill-time assays. The expression levels of mecA, mecR1, blaR1, and blaZ genes were measured by quantitative RT-qPCR. Additionally, the presence of the penicillin-binding protein 2a (PBP2a) protein of S. aureus and MRSA was evaluated by a Western blot assay. The results emphasized the fabrication of GA nanoparticles in spherical shapes with a diameter in the range of 40-50 nm. The data show that GA nanoparticles exhibit great bactericidal effectiveness against S. aureus and MRSA. The treatment with GA-NPs remarkably reduces the expression levels of the mecA, mecR1, blaR1, and blaZ genes. PBP2a expression in MRSA was significantly reduced after treatment with GA-NPs. Overall, this study demonstrates that glycyrrhizic acid nanoparticles have potent antibacterial activity, particularly against MRSA. This research elucidates the inhibition mechanism of glycyrrhizic acid, which involves the suppressing of PBP2a expression. This work emphasizes the importance of utilizing plant nanoparticles as effective antimicrobial agents against a broad spectrum of bacteria.